If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 + 6x + 8 = 0 Reorder the terms: 10 + 8 + 3x + 6x = 0 Combine like terms: 10 + 8 = 18 18 + 3x + 6x = 0 Combine like terms: 3x + 6x = 9x 18 + 9x = 0 Solving 18 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 9x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 9x = 0 + -18 9x = 0 + -18 Combine like terms: 0 + -18 = -18 9x = -18 Divide each side by '9'. x = -2 Simplifying x = -2
| -52/-13= | | (3x-4)(3x+4)=9x^2+6x-4 | | (-8)(5)(-3)= | | -(-6w+v)+(2v-w)=0 | | 2(x+3)+5(x-7)=41 | | (w+5)*(w-3)=0 | | 25-5d=d | | -30(-5)= | | 2(-4)(-6)= | | (-14)2= | | 3x+5(x-7)=41 | | (6)(-8)= | | 0.80x+0.50(8-x)=.10(-101) | | 2g-2+4g-9= | | Y=X[X-4] | | -21=x+10 | | (-6)(-9)= | | X-19=-43 | | 90+2x+x+15=180 | | (-2)(8)= | | 2x-9y-4=0 | | 3x^2+2x=12 | | 4-2x=5-x-1 | | .05d-3d+5=0 | | X+12+x=44 | | -4[X+2]=3[2X+1] | | 2(2x-3)=x+3(x-6) | | 6(x-2)=4-2x | | 4x^2+6x-8x^2=5 | | y=-1.3x-2 | | 13-2x=25 | | c^2=196 |